Comparative Analysis Between Using Google Meet and Gather Town Video Conferencing Platforms Viewed from User Experience Using meCUE Questionnaire on Students - Kusumawati, Nuur Roofiah; Efendi, Agus; Budiyanto, Cucuk Wawan (IJIE (Indonesian Journal of Informatics Education), 2024)
The purpose of this study was to determine the comparative results between using the Google Meet and Gather Town video conferencing platforms in terms of user experience using the meCUE questionnaire on students. This research is quantitative research with descriptive analysis and uses comparative study research methods. The data source of this research is High School in Malang. Sampling was taken randomly without regard to the strata in the population (simple random sampling) so that 4 classes consisting of 35 students were obtained. This research data collection technique adapts from a questionnaire instrument to assess the user experience of a service product such as a website or application. The meCUE questionnaire was created based on the Component model of User Experience (CUE) compiled by Thuering & Mahlke. The results of the data obtained through the meCUE questionnaire on the Google Meet and Gather Town video conferencing platform applications will be analysed so as to obtain results that can show the comparison of the two applications. The meCUE questionnaire provides automatic calculations using Microsoft Excel. Based on this research, it can be concluded as follows: (1) The Gather Town application has a better User Experience assessment than the Google Meet application. The overall indicator results on the Gather Town application show an average value of 4.6 where the value is higher than the Google Meet application with an average value of 3.3, (2) There is a difference between using the Google Meet and Gather Town video conferencing platforms in terms of User Experience using the meCUE Questionnaire for students (Sig. = 0.000 <0.05), (3) Google Meet and Gather Town platforms have their respective weaknesses and advantages that can be used alternately according to the learning method used by the teacher. The results of this study can be used as a reference in choosing video conferencing applications to be more effective and optimal in the learning process.